Ubiq-Ideas Machin: Ubiquitous computing system to support creative ideas generation sessions in open innovation [Ubiq-Ideas Machine: Sistema de cómputo ubicuo para apoyar sesiones creativas de generación de ideas en procesos de innovación abierta] (2014)
Ideas emerge in the less imagined scenarios, and it is mandatory to have a set of tools which ease their incorporation without time/place/access medium constraints, in order to maximize opportunities and avoid losing worthy contributions that become in incomes for innovations processes in companies or any other institution interested in actively involving their customers, employees, providers and other stakeholders in the Value Chain by means of co-creation. In this work we propose Ubiq-Ideas Machine, a ubiquitous computing prototype to support creative sessions of ideas generation by using a distributed scheme. This tool was built by reviewing literature and a strong field work with ubiquitous computing experts. We present the process until proposing the design and prototype generation. After a first assessment, an interesting projection is revealed due to a high commercialization impact.